2022
DOI: 10.1099/mgen.0.000838
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the Alpha variant of SARS-CoV-2 by the Delta variant in Lebanon between April and June 2021

Abstract: The COVID-19 pandemic continues to expand globally, with case numbers rising in many areas of the world, including the Eastern Mediterranean Region. Lebanon experienced its largest wave of COVID-19 infections from January to April 2021. Limited genomic surveillance was undertaken, with just 26 SARS-CoV-2 genomes available for this period, nine of which were from travellers from Lebanon detected by other countries. Additional genome sequencing is thus needed to allow surveillance of variants in circulation. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…In comparison with previous studies [28][29][30] [30], our results showed that the Alpha variant was detected in Akkar province, with a percentage of 6.8% of our sequences.…”
Section: Discussioncontrasting
confidence: 58%
“…In comparison with previous studies [28][29][30] [30], our results showed that the Alpha variant was detected in Akkar province, with a percentage of 6.8% of our sequences.…”
Section: Discussioncontrasting
confidence: 58%
“…This may affect not only the phylogenetic inference —since likelihood and Bayesian methods can use the ambiguity information— but also in other epidemiological analyses where finding the closest sequences may be challenging. Uvaia has been used successfully in both cases, by improving contact tracing and travel history inferences, and overall evolutionary analyses (Mashe, Takawira, de Oliveira Martins, et al ., 2021; Mashe, Takawira, Gumbo, et al ., 2021; Sarwar et al ., 2021; Aggarwal et al ., 2022; Eales, de Oliveira Martins, et al ., 2022; Merhi et al ., 2022), and here we present further details into the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…This program is also multithreaded, works in batches to avoid using up all available memory up, and can read from and write to compressed format. Uvaialign has been used in several SARS-CoV-2 analyses already (Mashe, Takawira, Gumbo, et al ., 2021; Sarwar et al ., 2021; Eales, de Oliveira Martins, et al ., 2022; Eales, Page, et al ., 2022; Merhi et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prioritizing COVID-19 vaccine doses in Lebanon was in accordance with the recommendations of the WHO Strategic Advisory Group of Experts (SAGE) framework for the allocation and prioritization of COVID-19 vaccination in targeting high-risk groups at different stages of vaccine supply availability [ 32 ]. Our patients were recruited during the circulation of the Alpha (January–April 2021), Delta (June–July 2021), and Omicron (December 2021–May 2022) variants of concern [ 33 , 34 ]. We categorized our study participants into two groups, as previously described [ 35 ].…”
Section: Methodsmentioning
confidence: 99%